Instructors’ Perceived Knowledge of Technological Pedagogical Content Knowledge (TPACK) at the Faculty of Education - Chukwuemeka, Emeka Joshua (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The use of technology in instruction has brought about different perceptions. The need to know how teachers integrate technology in instruction has brought along side different views. Therefore, this study mainly seeks to understand these views on instructors’ perceived knowledge of technological pedagogical content knowledge (TPACK) as it examines how their views changes according to gender, age, period of service, ranking, employment status, department, and the state of in-service training oriented towards the use of technology. In order to achieve the above aim, the researcher statistically examined Eastern Mediterranean University (EMU) Faculty of Education instructors’ perceived knowledge of TPACK. In this thesis, a TPACK survey instrument was administered to 53 instructors, a questionnaire was used to ascertain their perception levels across the seven TPACK dimensions. Mean, standard deviation, percentage, frequency and non-parametric tests (Mann Whitney U and Kruskal-Wallis test) were used for data analysis. The study reveals that instructors’ perceptions about TPACK were significantly high across all knowledge dimensions and there were statistical significant differences on how instructors viewed TPACK according to the above listed variables. These differences took place in Technological Knowledge (TK) and Pedagogical Content Knowledge (PCK) according to gender, Technological Knowledge (TK) according to age, Technological Knowledge (TK) according to period of service, Technological Knowledge (TK), and Technological Pedagogical Knowledge (PCK) according to employment status, Technological Knowledge (TK), Technological Pedagogical Knowledge (TPK) , and Technological Pedagogical Content Knowledge (TPACK) according to department and Pedagogical Content Knowledge (PCK) according to in-service training. There was no change according to ranking. Keywords: TPACK, Technological Pedagogical Content Knowledge, Perceived Knowledge of TPACK

Öz: Öğretimde teknolojinin kullanımı farklı algıların oluşmasına yol açmıştır. Öğretmenlerin öğretimde teknolojiyi nasıl bütünleştirdiklerini bilme gereksinimi farklı görüşleri beraberinde getirmiştir. Bu araştırmada öğretim görevlilerinin teknolojiye ilişkin pedagojik içerik bilgileri (TPACK) incelenmektedir. Araştırma öğretim görevlilerinin görüşlerinin cinsiyet, yaş, hizmet süresi, kıdem, sınıf, bölüm ve teknolojinin kullanımına yönelik hizmet içi eğitim açısından değişip değişmediği araştırılmıştır. TPACK veri toplama aracı Doğu Akdeniz Üniversitesi Eğitim Fakültesindeki 53 öğretim görevlisine uygulanmıştır. Ayrıca, öğretim görevlilerinin yedi bilgi alanındaki düzeylerini belirlemek amacıyla bir veri toplama aracı kullanılmıştır. Verilerin analizinde ortalama, standart sapma, yüzdelik, sıklık hesaplanmış ve parametrik olmayan testler (Mann Whitney U ve Kruskal-Wallis testi) kullanılmıştır. Çalışmada, öğretim elemanlarının TPACK algılarının tüm bilgi boyutları açısından anlamlı derecede yüksek olduğu ve yukarıda (daha önce) listelenen değişkenlere göre de, öğretim elemanlarının TPACK algılarında istatistiksel olarak anlamlı farklılıklar olduğu ortaya çıkmıştır. Bu farklılıklar, cinsiyete göre Teknolojik Bilgi (TK) ve Pedagojik İçerik Bilgisi (PCK), yaşa göre Teknolojik Bilgi (TK), hizmet süresine göre Teknolojik Bilgi (TK), istihdam durumuna göre Teknolojik Bilgi (TK), ve Teknolojik Pedagojik Bilgi (PCK), bölüm ve hizmet içi eğitime göre Pedagojik İçerik Bilgisi (PCK) Teknolojik Bilgi (TK), Teknolojik Pedagojik Bilgi (TPK) ve Teknolojik Pedagojik İçerik Bilgisi (TPACK) yer almıştır. Sıralamaya göre değişiklik olmadığı belirlenmiştir. Anahtar Kelimeler: TPACK, Teknolojik Pedagojik İçerik Bilgisi, TPACK’ın Algı Bilgisi
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2014. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education; Computer-assisted instruction; Internet in education; Education; Computer network resources; Educational Technology; Teaching; TPACK; Technological Pedagogical Content Knowledge; Perceived Knowledge of TPACK